Activation of Glucocorticoid Receptor Inhibits the Stem-Like Properties of Bladder Cancer via Inactivating the β-Catenin Pathway - Xu, Congcong; Sun, Mingwei; Zhang, Xiaozhen; Xu, Zhen; Miyamoto, Hiroshi; Zheng, Yichun (Frontiers in Oncology, 2020)
Background: Glucocorticoid receptor (GR) signaling pathway has been shown to involve epithelial -to- mesenchymal transition which was implicated in the regulation of bladder cancer stem cells (CSCs) in our previous study. Herein, we aim to figure out how GR affects the stem-like properties of bladder cancer cells. Methods: We used dexamethasone (DEX) treatment or gene-knockdown/-knockout techniques to activate or silence the GR pathway, respectively. Then we applied immunohistochemical staining and flow cytometry to assess the associations between the expression levels of GR and a stem cell surface marker CD44. Stem-like properties were assessed by reactive oxygen species (ROS), sphere-formation and side population assays. The expression levels of cancer stem cell-associated molecules were assessed by quantitative PCR and Western blotting. Tumor growth was compared using mouse xenograft models. Results: In GR-positive bladder cancer cells, DEX significantly reduced the expression of CD44 as well as pluripotency transcription factors including β-catenin and its downstream target (C-MYC, Snail, and OCT-4), the rate of sphere formation, and the proportion of side populations, and induced the intracellular levels of ROS. By contrast, GR silencing in bladder cancer cells showed the opposite effects. In xenograft-bearing mice, GR silencing resulted in the enhancement of tumor growth. Conclusions: These data suggested that GR activity was inversely associated with the stem-like properties of bladder cancer cells, potentially via inactivating the β-catenin pathway.